Mechanical evaluation of timber conservation processes by bending tests - Henriques, Dulce Franco (2018)
This paper presents the laboratory work performed with the purpose of understanding the mechanical performance of 340x20x20 mm maritime pine wood samples degraded by rot fungi when treated with a biocide product followed by consolidation through impregnation with a polymeric product. Four commercially available products were used: a water-based biocide, BC, a solvent-based biocide, X, an acrylic consolidant, PB (PB 72), and an epoxy-based consolidant, E. Seven sets of specimens each one having a varied range of fungal degradation were prepared. Then the product combinations were applied by brush to six sets of specimens (E, X-E, BC-E, PB, X-PB, BC-PB) of which one was left untreated for control, 0-0. Finally all sets were subjected to static bending strength test until rupture. Results showed that the acrylic and epoxy-based products lead to increased mechanical capacity of the consolidated wood up to 100% in some cases in specimens with 70% of MOE loss. The results presented the same order of magnitude for both wood consolidants. The previous application of biocide did not have a significant impact in the behavioral pattern of the consolidant: a marked improvement of the bending strength of the degraded specimens after treatment and consolidation. These results demonstrated the feasibility of combining biocide/consolidation products, and provide indications of interest to the application of this technique to extend the lifespan of wood elements moderately degraded by fungi in old buildings.